Un arrière-plan essentiel, la question de la sécurité dans la série Maria Vandamme - Isabelle Veyrat-Masson (Cahiers d’histoire.)
The television series, Maria Vandamme, was broadcast in 1989 and was a hit with audiences. It received numerous awards for its portrayal of the four-part adaptation of Jacques Duquesne's book, set during the Second Empire and concluding with La Commune de Paris. The protagonist, Maria, exhibits an unwavering passion for independence and defies her societal position, actively eluding aggression from men and government agents. Through the assistance of a few loyal friends, she manages to escape from her dire situation, even as she confronts the police, who shields neither her nor her loved ones, instead committing brutalities against them. Despite their unjust actions, these upholders of order keep driving the narrative forward, but never to a climactic point. Each of their destinies still comes to fruition, despite the repressive conditions and the events that shape them.